2017
DOI: 10.20944/preprints201703.0087.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Zika Virus by Marine Algae

Abstract: For many years marine algae has been subject of numerous researches and as a source of natural products with antiviral activity, such as terpenes, alkaloids and sulphated polysaccharides. However, the anti-Zika virus (ZIKV) potential of algae has not been studied. In this study we evaluated extracts seven species of the three major classes of seaweeds (Phaeophyceae, Chlorophyceae and Rhodophyceae) against ZIKV. All seaweeds tested are native of the Brazilian coast, except for Kappaphycus alvarezii that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A study was conducted on the antiviral treatment of Zika virus (ZIKV), which presented the inhibition of C. racemosa towards ZIKV replication in a dose-dependent manner. The study found that C. racemosa extract exhibited the highest cytotoxicity (CC 50 ) effect, 732 µg/mL against ZIKV (Cirne-santos et al, 2017). It can be said that Chlorophyta extracts can be a promising species for further studies for the development of new antiviral agents.…”
Section: Biological Activities Of Chlorophytamentioning
confidence: 97%
“…A study was conducted on the antiviral treatment of Zika virus (ZIKV), which presented the inhibition of C. racemosa towards ZIKV replication in a dose-dependent manner. The study found that C. racemosa extract exhibited the highest cytotoxicity (CC 50 ) effect, 732 µg/mL against ZIKV (Cirne-santos et al, 2017). It can be said that Chlorophyta extracts can be a promising species for further studies for the development of new antiviral agents.…”
Section: Biological Activities Of Chlorophytamentioning
confidence: 97%
“…We have already published a paper, which demonstrates that the algae extract of C. racemosa presents a 732 mg/mL CC 50 . 26…”
mentioning
confidence: 89%
“…The search for drugs that act at different stages of viral replication in addition to its low toxicity may be important to determine if it is possible to adopt it for clinical use. 26 In this way, when we observed the low cytotoxicity and high inhibition of the replication of CHIKV, we evaluated the inhibitory effect of the compound added at different times after viral infection. We observed that caulerpin added in time 0, 1, 2, and 3 hours postinfection still maintains an inhibitory potential of viral replication 100% for CHIKV.…”
Section: Time Of Addition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Norris species is characterized as a robust plant (Rhodophyta, Ceramiales, Rhodomelaceae), which can measure from 10 to 15 cm in height, with flat apices of 3 to 4 mm wide, showing dark red coloration (Carvalho et al, 2006). Several biological activities have been described from O. obtusiloba, mainly for their extracts, such as the fraction of O. obtusiloba rich in lectin that inhibited the trypsin and α-amylase enzymes, indicating its potential use in the production of drugs against diabetes (de Oliveira et al, 2009) or the ethanol extract that was able to inhibit the replication of Zika virus while maintaining low cytotoxicity (CC 50 =525 µg/ml) (Cirne-Santos et al, 2017). Antiviral activity against HSV-1 and HSV-2 has also been described for glycolipids extracted from O. obtusiloba (de Souza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%